Keragaman Spesies Kupu-Kupu (Lepidoptera) Sebagai Objek Pengembangan Ekowisata TWA Suranadi Dan Upaya Penyusunan E-Modul Ekologi Hewan - Efendi, Ismail; Karmana, I Wayan; Adawiyah, Siti Rabiatul; Arifin, Ahmad Aris (Bioscientist : Jurnal Ilmiah Biologi, 2024)
The purpose of this study is to identify the diversity of butterfly species as a potential object for ecotourism development in the TWA Suranadi and to develop an animal ecology e-module. This research is a descriptive exploratory study. Data collection was conducted using survey techniques, and samples were taken using Purposive Random Sampling by dividing the TWA Suranadi area into four transects (water transect, left transect, middle transect, and right transect). Butterfly collection was carried out using the sweeping technique implemented randomly. The development of the animal ecology module was designed using the 4D model (Define, Design, Develop, and Disseminate). The Develop phase was limited to expert validation to assess the content validity and construct validity of the animal ecology e-module. The results showed that butterfly diversity varied across the observation transects. The Middle Transect dominated with a high distribution percentage of 56.25%, followed by the Water Transect at 23.43%, the Left Transect at 15.62%, and the Right Transect with the lowest distribution percentage at 4.7%. Ecological analysis results indicated a species diversity index across the four research locations ranging at 2.341 (Moderate Diversity), an evenness index ranging from 0.152 (Low Evenness), and a dominance index of 0.108 (Low Dominance). Expert validation results showed that the content validity of the animal ecology e-module had an index of 0.880, categorized as very valid, while the construct validity, which included the feasibility of presentation, had an index of 0.902, categorized as very valid, and the feasibility of language aspect averaged at 0.770, categorized as valid.